Heroes of the environment : true stories of people who are helping to protect our planet - Rohmer, Harriet; McLaughlin, Julie (San Francisco : Chronicle Books, 2009)
Profiles the lives and accomplishments of twelve environmentalists from United States, Canada, and Mexico; and describes a teenage girl who sought to remove an industrial pollutant from the Ohio River, a Mexican wrestler who acts as an advocate for turtles and whales, and more.
Map on endpapers.
6.7
3-6
3-6
Keywords: Environmentalists -- Biography -- Juvenile literature; Environmentalists; Environmentalists -- Biography